Peran Analisis Retorika Semit dalam Studi Al-Qur’an dan Penguatan Toleransi Beragama - Mohammad Yusuf Setyawan (2022)
The emergence of Semitic rhetoric is based on two opposing orientations in assessing the unity of the language structure of the Qur'an. Classical and modern Islamic studies argue that the structure of the Qur'an contains unity and harmony. Meanwhile, most orientalism studies consider that the structure of the Qur'an contains disintegration and is incoherent so that it is necessary to reorder it to fit the logic. Cuypers assumes that the reason for the orientalists' judgments is that they measure the structure of the Qur'an with Greek rhetoric that does not match the structure of the language of the Qur'an. According to him, the structure of the Qur'an needs to be studied through an analysis of Semitic rhetoric. This article aims to reveal the role of Semitic rhetoric analysis on the coherence of the verses of the Qur'an as well as strengthening religious tolerance between religious communities, especially Islam, Christianity, and Judaism. This analysis is used to understand the variations in rhetorical style and language structure of the Qur'an in the historical context of the revelation of the holy book. At first this method was used as an approach to Torah and Bible texts. This research is a qualitative type using analytical descriptive method. Through this research, the researcher finds that Semitic rhetoric can be a new alternative in interpreting the verses of the Qur'an, as this analysis has been previously applied to the holy books of Jews and Christians. In addition, the use of analysis can also be used as a medium for strengthening tolerance between the three religious communities because it is based on the similarity of the structure of each holy book that is in the Semitic language family. This Cuypres study can be used as an important capital to strengthen religious tolerance after the COVID-19 pandemic.